The effect of successor related factors on business continuity on agrobased Smes in Malaysia - Mansor, Zuraina; Hossan, Dalowar (Karadeniz Technical University, 2021)
Succession planning is part of human resource plan that is becoming a hot topic as it is very important to support the business continuity. However, many businesses failed to plan their successor well especially the small medium enterprises (SMEs) which also causing the business continuity at risk. According to past researches, small firms mostly found to be unable to sustain and often struggle to retain key employees. In this study, we focused on the successor-related factors relevant to SMEs in determining business continuity. Based on the literature review it was found that the issue received very limited attention. The study also examined the moderation effect of company’s age in the relationship between successor’s related factors and business continuity. The study has distributed 400 questionnaires to Agro related SMEs in Malaysia, and however, 113 sets of questionnaires were successfully returned. Data was analysed using SEM-AMOS and the findings showed that succession planning has positive significant effect on business sustainability while company’s age does not moderate the relationship between succession planning and business sustainability. The findings could assist managers and higher authority of SMEs to plan and recognized the impact of successors related factors in determining the business continuity.